Evaluación de la respuesta inmunitaria en terneras con la aplicación de propóleo, polen y miel en el cantón Mejía, provincia de Pichincha hacienda Mayrita - Heredia Jaguaco, Luis Enrique (2015)
In this researd was conducted in the Pichincha Province Mejia Canton Mayrita Farm a serological survey to determine the amount of immunoglobulin type A, G, y M, in calves of three days old , using 3 different compounds (pollen, propolis, honey) added milk 10%, with the aims of increasing the percentage of immunoglobulins in the animal. The blood samples for the study were taken at the beginning of the investigation before application of treatments and second sample at the end of the implementation there of, the samples were obtained by puncture in the sacral vein with a needle Vacutainer in an amount of 5 ml per animal that were placed in tubes and sent to the laboratory Vet Lab….